Supervisi Akademik Pada Guru Pendidikan Agama Hindu Smp Di Kabupaten Karangasem - Ni Made Indiani; Ni Putu Suwardani (Jayapangus Press, 2020)
Effective schools are usually led by effective principals. The school principal is assisted by a supervisor to improve the quality of the school. Therefore both are required to have many competences, visionary, in order to be able to direct teachers at the education unit level. This study aims to examine the role of academic supervision in junior high schools in the Karangasem area. Through a qualitative approach, data is obtained by interviewing several informants, observing and studying literature. The results obtained that 1) Academic supervision is carried out by the principal and school supervisors. 2) Academic supervision is considered to play an important role because it is a synergy of works and responsibilities between Hindu religious education teachers, school principals, and school supervisors in order to achieve quality education. 3) The Quality education is determined by the skills of teacher in teaching both in terms of developing learning programs, increasing the ability/competence of these teachers through various innovations made and empowering other supporting factors such as utilizing the school environment to achieve harmonious learning goals.